Characterization of Specialized Homegardens in Terms of Technology Needs and Techno-Socio- Economic Dimensions - Ravikishore, Modem; Thomas, Allan; Krishnan, Rahul (International Journal of Bio-resource and Stress Management, 2017)
This research paper focuses on characterization of homegardens in terms of technology needs and techno-socio-economic dimensions. The study location was Central Kerala region consisting of Thrissur, Palakkad and Ernakulam districts of India due to the presence of specialized homegarden system. A total of 30 homegarden farmers were selected, to assess the homegardens in terms of technology needs. The study also covered the same Central Kerala region to assess the techno-socio-economic dimensions as perceived by homegarden farmers, Agricultural Officers and Scientists. With respect to technology needs of specialized homegarden farmers, a Chi square test was performed and the interpretation was that, the distribution, by and large had the same technology needs as far as the perception of the farmer was concerned. In general, technology needs of the farmers had radically changed from the conventional ones to those of technologies like scientific storage, processing and value addition of homegarden produces. Technological, economical and socio-cultural dimensions related to the specialized components in homegardens show a variation in priorities between the specialized homegarden farmers and the Agricultural Officers and Scientists. Some of the dimensions which were of high relevance to the homegarden farmers were considered rather insignificant to the other section. Based on the results, it is imperative to identify the dimensions that were perceived to be important to all categories of respondents for providing economic, ecological, social and cultural benefits to the individual farmer and to the community.